A discussion on the location of the anterior and posterior thoracic spiracles on Coccinea (Bollettino di zoologia agraria e bachicoltura, 2024)
In the superfamily Coccoidea, the number of thoracic spiracles is reduced to two pairs. On members of most scale insect families, these pairs of spiracles are generally considered to be located either near the anterior margins of the mesa- and metathorax or in the intersegmental furrows between the proand mesothorax and between the mesa- and metathorax. However, on Diaspididae, the anterior pair- of spiracles is here considered to have migrated onto the prothorax.
Keywords: Coccoidea; mesothoracic spiracles; metathoracic spiracles; location